Zinc‐Air Batteries: Facilitated Oxygen Chemisorption in Heteroatom‐Doped Carbon for Improved Oxygen Reaction Activity in All‐Solid‐State Zinc–Air Batteries (Adv. Mater. 4/2018). Issue 4 (22nd January 2018) - Liu, Sisi; Wang, Mengfan; Sun, Xinyi; Xu, Na; Liu, Jie; Wang, Yuzhou; Qian, Tao; Yan, Chenglin
Abstract : In article number1704898, Tao Qian, Chenglin Yan, and co‐workers report a highly‐efficient hybrid electrode with metal–organic‐framework‐derived holey nanocrystals grown in situ on the graphene framework for direct use in zinc–air batteries, showing outstanding electrocatalytic activities for oxygen reactions. Facilitated chemisorption of oxygen molecules and oxygen‐containing intermediates on the heteroatom‐doped carbon is observed by in situ characterization during battery operation.